2021
DOI: 10.1038/s41598-021-90610-y
|View full text |Cite
|
Sign up to set email alerts
|

Urine biomarkers for the prediction of mortality in COVID-19 hospitalized patients

Abstract: Risk factors associated with severity and mortality attributable to COVID-19 have been reported in different cohorts, highlighting the occurrence of acute kidney injury (AKI) in 25% of them. Among other, SARS-CoV-2 targets renal tubular cells and can cause acute renal damage. The aim of the present study was to evaluate the usefulness of urinary parameters in predicting intensive care unit (ICU) admission, mortality and development of AKI in hospitalized patients with COVID-19. Retrospective observational stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 38 publications
4
20
1
1
Order By: Relevance
“…The predictive model was included and it was shown that LDH can be a useful tool in the management of patients requiring hospitalisation for a SARS‐CoV‐2 infection. 14 In our study, age (OR: 1.06, 95% CI 1.03‐1.10, P = .035), respiratory rate ≥ 30 breaths/min (OR: 4.72, 95% CI 1.26‐6.24, P < .0031), SpO 2 ≤ 93% (OR: 3.82, 95% CI 1.18‐5.82, P = .001) and proteinuria (OR: 1.13, 95% CI 1.02‐2.1, P = .023) were independent predictive factors for disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…The predictive model was included and it was shown that LDH can be a useful tool in the management of patients requiring hospitalisation for a SARS‐CoV‐2 infection. 14 In our study, age (OR: 1.06, 95% CI 1.03‐1.10, P = .035), respiratory rate ≥ 30 breaths/min (OR: 4.72, 95% CI 1.26‐6.24, P < .0031), SpO 2 ≤ 93% (OR: 3.82, 95% CI 1.18‐5.82, P = .001) and proteinuria (OR: 1.13, 95% CI 1.02‐2.1, P = .023) were independent predictive factors for disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…Despite tubular injury being the predominant pathologic lesion, proteinuria and hematuria appear to be relatively prominent in COVID-19-associated AKI [7,15,17,24,31,32]. Specifically, >40% of patients hospitalized for COVID-19 have proteinuria when assessed by qualitative urinalysis [7,15,32,81,82]. Similarly high rates of proteinuria were observed in two studies in which patients admitted with COVID-19 underwent quantitative proteinuria assessment, with 19 (83%) of 23 patients (of which 12 developed AKI) having proteinuria >150 mg per g creatinine in one study and 33 (63.5%) of 52 patients (of which 34 developed AKI) having albuminuria of >30 mg per g creatinine in the other [24,83].…”
Section: Hemoproteinuria In Covid-19-associated Akimentioning
confidence: 99%
“…Although several studies reported proteinuria and hematuria in conjunction with COVID-19 infection [ 7 16 ], only a few evaluated differences in the incidence of proteinuria and hematuria on dipstick urinalysis in patients with AKI as compared to those without AKI [ 9 11 , 13 , 17 ]. Even fewer studies investigated the association between proteinuria and hematuria with development of AKI and need for RRT [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…One study reported that a urine protein-to-creatinine ratio (UPCR) ≥ 1 g/g on admission was associated with an increased risk of requiring RRT; albeit, these results may not be readily generalizable as UPCR is not one of the commonly obtained laboratory tests at admission [ 18 ]. Most of the other studies had small sample sizes, ranging from 129–307 total participants [ 8 , 16 , 19 , 20 ], and two did not have a non-AKI control group [ 12 , 21 ]. A larger, recently published study reported that presence of proteinuria and hematuria ≥ 1 + was associated with an increased risk of AKI [ 17 ] but did not exclude AKI present on admission, limiting the ability to predict development of AKI during hospitalization with COVID-19.…”
Section: Introductionmentioning
confidence: 99%